Universal scaling in Bardeen-Cooper-Schrieffer superconductivity in two dimensions in non-s waves - Adhikari, S. K.; Ghosh, A. (Iop Publishing Ltd, 1998)
The solutions of a renormalized BCS model are studied in two space dimensions for s, p and d waves for finite-range separable potentials. The gap parameter, the critical temperature T-c, the coherence length xi and the jump in specific heat at T-c as a function of the zero-temperature condensation energy exhibit universal scalings. In the weak-coupling limit, the present model yields a small xi and large T-c, appropriate for high-T-c cuprates. The specific heat, penetration depth and thermal conductivity as functions of temperature show universal scaling for p and d waves.